ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI CUSTOMER LOYALTY MELALUI CUSTOMER SATISFACTION (STUDI PADA PELANGGAN INDIHOME DI KOTA SEMARANG) - Puspitasari, Sisca Willy; Astuti, Sri Rahayu Tri (Faculty of Economics and Business Diponegoro University, 2019)
This study aims to analyze the perceived price, perceived quality and service quality for customer loyalty through customer satisfaction on Indihome customers in Semarang City. The population used in this study is Indihome customers in Semarang City. The number of samples used in the study were 100 respondents. The method of data collection was done using a questionnaire. This study uses multiple linear regression analysis techniques using the SPSS 21 analysis tool.Research uses the theory of consumer behavior and strategic marketing. The results showed that perceived price has a positive and significant effect on customer satisfaction, perceived quality has a positive and significant effect on customer satisfaction, servic quality has a positive and significant effect on customer satisfaction, and customer satisfaction has a positive and significant effect on customer loyalty.